Comparison of Growth Performance, Carcass Characteristics and Meat Quality of Korean Local Chickens and Silky Fowl - Y. K. Choo; H. J. Kwon; S. T. Oh; J. S. Um; B. G. Kim; C. W. Kang; S. K. Lee; B. K. An (Asian-Australasian Journal of Animal Sciences, 2014)
This study was conducted to compare growth performance, carcass characteristics and meat quality of 4 breeds of local chicken. A total of 480 1-d-old chicks were distributed to 16 pens, with 4 treatments of breed, 4 replicates and 30 chicks per pen. Three Korean local breeds of white-mini broiler, Hanhyup-3-ho, and Woorimatdag, and a breed of silky fowl were raised under identical rearing and feeding conditions for 31-d, 37-d, 36-d, and 59-d, respectively. The BW and feed consumption on a pen basis were weekly measured for all pens, and ADFI, ADG and gain:feed were calculated for each pen. The ADFI and ADG of 3 breeds of Korean local chicken were greater than those of silky fowl (p<0.05). Within the Korean local breeds, ADFI of white-mini broiler was the highest (p<0.05), and ADG of Hanhyup-3-ho and white-mini broiler was the highest (p<0.05). Gain:feed of silky fowl was less than that of the 3 breeds of Korean local chicken. The carcass and breast yield of white-mini broiler were the greater than those of other breeds (p<0.05). The breast meat color (CIE L*, a*, and b*) of 3 breeds of Korean local chicken were higher than that of silky fowl (p<0.05). The breast meat of Hanhyup-3-ho had greater cooking loss (p<0.05), whereas water holding capacity and pH were less than those of other breeds (p<0.05). The color score of 3 breeds of Korean local chicken was higher than that of silky fowl (p<0.05). Woorimatdag had a higher score on tenderness (p<0.05), whereas flavor score was less than that of other breeds (p<0.05). In conclusion, 4 local breeds of chicken have some unique features and seem to have more advantages, and this information can help consumers who prefer healthy and premium chicken meat.